Assesing local community to Existence of Local Marine Sanctuary “Kawasan Kelola Laut” in Saponda Island, Konawe Regency, Southeast Sulawesi - Baru Sadarun; Subhan Subhan (AQUASAINS, 2021)
The study was conducted between February and June 2020. The pesence of local institution, which is responsible for marine and fisheries resource management known as “Kawasan Kelola Laut (KKL*)”, was the main reason why the study was carried out in Saponda Island. The objective of the study was to assess communtity preception on the presence of KKL*. Cluster random sampling method was selected by involving 94 respondents as representative of the perception. Principal component analysis (PCA) was selected, through which the relation between each respondent charateristic and level of perception was indentified. Result showed that respondent perception had positively correlated to meeting frequency (r = 0.67). the higher frequency of participant attended either formal or non-formal meeting, the better community perception would be formed. It was estimated thar respondent received more information and socializaton on the essential of KKL* during the meeting.Keywords: Perception, Kawasan Kelola Laut, Saponda Island